Studi Deskriptif Tentang Kondisi Fisik Siswa Kelas VI SD Negeri 15 Lasusua Tahun Ajaran 2025/2026 - Siti Sulfirani; Zakaria Zakaria; Yun Angraeni Saputri (Universitas Muhammadiyah Kolaka Utara, 2025)
The problem in this study is related to the physical condition of the sixth-grade students at SD Negeri 15 Lasusua for the 2025/2026 academic year. This study aims to determine the level of students' physical fitness. The method used is a survey with test and measurement techniques using the Indonesian Physical Fitness Test (TKJI) for ages 10–12 years, which includes a 600-meter run test (endurance), a 60-second sit-up test (abdominal muscle endurance), vertical jump (leg power), 40-meter sprint (speed), and a 10-second burpee test/squat thrust (agility). The research population consisted of all sixth-grade students at SD Negeri 15 Lasusua for the 2025/2026 academic year, using a saturated sampling technique, so the entire population was used as a sample totaling 26 students, consisting of 15 boys and 11 girls. The research results show that the students' physical fitness level falls into the good category at 19.23% (5 students), the moderate category at 57.69% (15 students), and the poor category at 23.07% (6 students). Therefore, it can be concluded that the physical fitness level of the sixth-grade students at SD Negeri 15 Lasusua in the 2025/2026 academic year is generally in the moderate category.